2017
DOI: 10.4149/bll_2017_059
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive guide to telocytes and their great potential in cardiovascular system

Abstract: Telocytes, a recently discovered type of interstitial cells, have a very distinctive morphology -the small cell body with long extensions, named telopodes. In our review, apart from introducing general aspects of telocytes, we focus on properties, functions and future potential of those cells in cardiovascular system. However, physiological functions of telocytes in cardiovascular system are still regarded as quite enigmatic. Previous studies claim that they play a role in organogenesis and regeneration, bioel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
(136 reference statements)
0
30
0
3
Order By: Relevance
“…Some authors consider them the second longest processes in the human body after neuronal axons, with lengths of up to hundreds of micrometers (Cretoiu et al 2012). The cell body is usually described as either pear-shaped, spindle-shaped, triangular or even stellate, depending on the number of processes (Kucybala et al 2017). In contrast to their remarkable length, telocyte processes are only approximately 0.2 μm thick, which makes them undetectable using only a light microscope.…”
Section: Question 1 Are Telocytes Truly An Individual/unique/new Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors consider them the second longest processes in the human body after neuronal axons, with lengths of up to hundreds of micrometers (Cretoiu et al 2012). The cell body is usually described as either pear-shaped, spindle-shaped, triangular or even stellate, depending on the number of processes (Kucybala et al 2017). In contrast to their remarkable length, telocyte processes are only approximately 0.2 μm thick, which makes them undetectable using only a light microscope.…”
Section: Question 1 Are Telocytes Truly An Individual/unique/new Celmentioning
confidence: 99%
“…Therefore, it is advantageous to be familiar with the antigens that are typically expressed in these cell populations. Telocyte, fibroblast, pericyte and neuron positivity for the five antigens commonly used to detect telocytes was summarized and compared by Kucybala et al (2017). Detailed immunohistochemical profiling revealed that telocytes are positive for approximately ten additional antigens as well as the five most frequently used antigens (Aleksandrovych et al 2017).…”
Section: Question 3 Is It Possible To Identify Telocytes Using Monocmentioning
confidence: 99%
“…Also, myocardial infarction (MI) is one of the leading causes of death in both men and women (1, 2). Previous reports have indicated that during ischemic injury, oxidative stress produced by generation of reactive oxygen species plays an important role in the development of MI (3,4). Several researchers have reported the signifi cant contribution of oxidative stress to the development of cardiovascular diseases, including ischemic injury and MI (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Уменьшение ОП Тц в миокарде у пациентов с неблагоприятным исходом КШ сопровождалось достоверным уменьшением трофического индекса и увеличением индекса Керногана, что косвенно может свидетельствовать об участии Тц в ангиогенезе. Данное предположение делают и другие исследователи в своих работах [18]. Manole C. G. с соавт.…”
Section: Discussionunclassified
“…Существует гипотеза, что Тц могут влиять на скорость и ритмичность генерации импульса в миокарде. Было показано, что уменьшение их количества может приводить к развитию аритмий [18]. Другой особенностью сердечных Тц является их мультифенотипичность.…”
Section: Discussionunclassified